The Impact of Aristotelianism on Modern Philosophy - Pozzo, Riccardo, 1959- (Book collections on Project MUSE., 2004)
"In this volume, thirteen distinguished scholars consider the impact of Aristotelianism on modern philosophy. Spanning the last five centuries, the articles examine Aristotelian issues present in the writings of late scholastic, Renaissance, and early modern philosophers, such as: Vernia, Barbaro, Cajetan, Nifo, Piccolomini, Zabarella, Galileo, Campanella, Semery, Leibniz, Rousseau, Kant, Hegel, Nietzsche, Husserl, Heidegger, Wittgenstein, and Gadamer. They trace the impact of the tradtion of Renaissance Aristotelianism, which was first molded by Manuzio's edition of Aristotle's Opera, found its standing in the monumental edition of the Giunti with Averroes' commentary, and reached its blossoming by means of the European diffusion of the works of the Paduan School, first and foremost of Zabarella." "The contributors pay particular attention to the role of the five intellectual virtues set forth by Aristotle in book VI of the Nicomachean Ethics - art, prudence, science, wisdom, and intellect - in modern philosophy."--Jacket